The Development of Students' Understanding of Science - Vosniadou, Stella (Frontiers in Education, 2019)
Children construct intuitive understandings of the physical world based on their everyday experiences. These intuitive understandings are organized in skeletal conceptual structures known as framework theories. Framework theories are different from currently accepted science and impose constraints on how students understand the scientific explanations of phenomena causing the creation of fragmented or synthetic conceptions. It is argued that in order to understand science students need to make important changes in the way they represent and explain the physical world as well as in their ways of reasoning. During the development of science knowledge students must also create new concepts and new belief systems which do not necessarily supplant their framework theories but co-exist with them. These developments are gradual and slow and follow a learning progression. In order to be effective science education needs to make students aware of their intuitive understandings, provide scientific information gradually and in agreement with students’ learning progressions and develop students’ reasoning abilities and executive function skills.